PFI-1, a highly selective protein interaction inhibitor, targeting BET Bromodomains. - Picaud, S; Da Costa, D; Thanasopoulou, A; Filippakopoulos, P; Fish, P; Philpott, M; Fedorov, O; Brennan, P; Bunnage, M; Owen, DR; Bradner, J; Taniere, P; et al. (2013)
Bromo and extra terminal (BET) proteins (BRD2, BRD3, BRD4, and BRDT) are transcriptional regulators required for efficient expression of several growth promoting and antiapoptotic genes as well as for cell-cycle progression. BET proteins are recruited on transcriptionally active chromatin via their two N-terminal bromodomains (BRD), a protein interaction module that specifically recognizes acetylated lysine residues in histones H3 and H4. Inhibition of the BET-histone interaction results in transcriptional downregulation of a number of oncogenes, providing a novel pharmacologic strategy for the treatment of cancer. Here, we present a potent and highly selective dihydroquinazoline-2-one inhibitor, PFI-1, which efficiently blocks the interaction of BET BRDs with acetylated histone tails. Cocrystal structures showed that PFI-1 acts as an acetyl-lysine (Kac) mimetic inhibitor efficiently occupying the Kac binding site in BRD4 and BRD2. PFI-1 has antiproliferative effects on leukemic cell lines and efficiently abrogates their clonogenic growth. Exposure of sensitive cell lines with PFI-1 results in G1 cell-cycle arrest, downregulation of MYC expression, as well as induction of apoptosis and induces differentiation of primary leukemic blasts. Intriguingly, cells exposed to PFI-1 showed significant downregulation of Aurora B kinase, thus attenuating phosphorylation of the Aurora substrate H3S10, providing an alternative strategy for the specific inhibition of this well-established oncology target.